Social sustainability skills in secondary education: gender and spatial contexts - Deepanjana Chakraborty; Tanu Shukla; Virendra Singh Nirban (Institute of Advanced Engineering and Science, 2024)
In today’s rapidly evolving world, the acquisition of social competencies and an understanding of sustainability principles are critical for holistic student development. This study delves into the comprehensive analysis of social and sustainable skills within the framework of secondary education, considering the influential factors of gender and spatial contexts. To investigate whether there exists a difference between the students at the secondary level of education in social and sustainable skills along the demographic lines of gender and spatial context. A primary data collection method was used for gathering quantitative data from 125 students on a Likert-type 25-item self-constructed questionnaire and differential analysis was conducted. The performance of male and female students is significantly different and the performance of students in the urban settings is higher than the students in the rural settings. It shows that female and rural students are comparatively lower in performing on the social and sustainable skills test. The findings of this research hold implications for educators, policymakers, and practitioners committed to fostering well-rounded individuals prepared for the challenges of the 21st century. By identifying gender-specific patterns and spatial influences, stakeholders can tailor educational strategies and interventions to ensure equitable skill cultivation.